Neuromuscular Blockade for Cardiac Arrest Patients Treated With Targeted Temperature Management: A Systematic Review and Meta-Analysis - Lin, Tong; Yao, Yan; Xu, Yuan; Huang, Hui-Bin (Frontiers in Pharmacology, 2022)
Background: Neuromuscular-blocking agents (NMBA) are often administered to control shivering in comatose cardiac arrest (CA) survivors during targeted temperature management (TTM) management. Thus, we performed a systematic review and meta-analysis to investigate the effectiveness and safety of NMBA in such a patient population. Methods: We searched for relevant studies in PubMed, Embase, and the Cochrane Library until Jul 15, 2021. Studies were included if they reported data on any of the predefined outcomes in adult comatose CA survivors managed with any NMBA regimens. The primary outcomes were mortality and neurological outcome. Results were expressed as odds ratio (OR) or mean difference (MD) with an accompanying 95% confidence interval (CI). Heterogeneity, sensitivity analysis, and publication bias were also investigated to test the robustness of the primary outcome. Data Synthesis: We included 12 studies enrolling 11,317 patients. These studies used NMBA in three strategies: prophylactic NMBA, bolus NMBA if demanded, or managed without NMBA. Pooled analysis showed that CA survivors with prophylactic NMBA significantly improved both outcomes of mortality rate (OR 0.50; 95% CI 0.37-0.67; I2=19%; P<0.00001) and neurological outcome (OR 0.53; 95% CI 0.37-0.78; I2=59%; P=0.001) without adversely affecting other outcomes than those managed without NMBA. These results were confirmed by the sensitivity analyses and subgroup analyses. Only a few studies compared CA survivors receiving continuous versus bolus NMBA if demanded strategies and the pooled results showed no benefit in all the predefined outcomes between the two groups. Conclusions: Our results showed that using prophylactic NMBA strategy compared to the absence of NMBA was associated with improved mortality and neurologic outcome in CA patients undergoing TTM. However, more high-quality randomized controlled trials are needed to confirm our results.